IMPLEMENTASI HOTSPOT SERVER DAN MANAJEMEN BANDWIDTH MENGGUAKAN PCQ PADA MIKROTIK - putra, Eka Syah (Computer Science and Industrial Engineering, 2021)
Lajau Kopi, is a cafe located in Batu Aji, Batam. internet is very important to increase their services to attract visitors. that way the internet they provide can improve service so that it adds to the cafe's profits the. the number of users who access the network makes a wifi network they provide becomes unstable because the network they provide is not have good bandwidth management. with a total bandwidth used as much as 20 Mbps and the large number of users make the hotspot network very slow and unstable. This study aims to reduce the problem of division of bandwidth that is in the coffee lagoon. By using the method per connection queue (PCQ) in mikrotik the researcher hopes to solve the problem of sharing bandwidth in the coffee lajau hotspot network. using PCQ as a bandwidth management method very suitable for public places that require stability in use Internet. This method divides the total bandwidth evenly and fairly to each user with a 20 Mbps scheme if there are 4 users, the bandwidth you get each users at 10 Mbps. by using an existing dimikrotik torch to monitoring the results of the distribution of bandwidth.